The derivational family of the noun SAULĖ - Vaskelienė, Jolanta; Girdvilytė, Greta (Lietuvių kalba, 2020)
The word saulė (‘the sun’) and the denotation indicated by it has a lot of meanings in the Lithuanian culture: the mythologists, philosophers, art critics, and literature critics have written about this phenomenon. The article analyses the derivational family of the noun saulė. Having analysed the derivatives with the root word saul (or one of the root words) found in various sources and the relations between them, the following conclusions have been drawn.The derivational family, the centre of which is the noun saulė, consists of 287 derivatives: mostly nouns (78 per cent of all derivatives), adjectives (15 per cent), verbs (4 per cent) and adverbs (3 per cent). First degree derivatives are dominant, i.e. such derivatives whose underlying word (or one of them) is the noun saulė: cf. first degree derivatives make 74 per cent of all derivatives, and 26 per cent of all derivatives of further derivation stages.The nouns are formed by using all derivational types; however, the compound nouns prevail: they make 69 per cent of all noun derivatives. 61 per cent of compounds are with the second verbal component. The components of 34 per cent of compounds are linked with the vowel -ė-. Some compounds have direct meanings (they denote purpose and place), and many more compounds have figurative meanings (metaphorical and metonymic). The noun saulė almost always (99 per cent) is the first component of the first degree compounds.There are a few neologisms – the derivatives or the derivatives that have acquired a new meaning – in the derivational family of the noun saulė. New realia are named as neologisms or they are variants and synonyms of derivatives incorporated in dictionaries.The research revealed that, in the Lithuanian language, the same entities (mostly plants, phenomena) are named in terms of variation: 40 rows of derivational variants (DV) and 33 rows of derivational synonyms (DS) have been formed and discussed. The plant saulėgrąža (‘a sunflower’) and the time when the sun sets down saulėlydis (‘the sunset’) have a particularly high number of conjugate names: in these rows of DV and DS, there are 33 and 29 derivatives, respectively. Although in many cases DV and DS are the words of a close (or even identical) semantical meaning, their usage and frequency differ: usually only one member of the DV and the DS row is common to the contemporary Lithuanian language, it is often used, while other derivatives often belong to the passive lexis and are known to a small part of the Lithuanian language users, or are recorded in written sources. In rare cases, conjugate derivatives are related in terms of antonyms.
Keywords: derivational family; derivative; compound; derivational variants; derivational synonyms